Pengembangan Aplikasi Pelaporan Modul Penerimaan Negara Generasi 2 (MPN G-2) Menggunakan Digital Signature pada PT. Bank BNI Syariah - Ahmad Muharria Rajhasla Putra; Wendi Usino (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Politeknik Pratama Mulia Surakarta, 2016)
As one of the bank of perception, BNI Syariah has a duty not only to develop the payment system but also to require submitting a report to the Ministry of Finance. There are two things to be reported, namely the report on H + 0 and report on H + 1. Report on H + 0 consists of DNP Reports (Daftar Nominatif Penerimaan) and LHP (Laporan Harian Penerimaan). Both reports should be submitted in text file format. Report on H + 1 is report of Bank Statement (BS) or Rekening Koran report that contains transaction based on bank systems. This research describes about development MPN G-2 reporting at PT. BNI Syariah by implementing digital signature with RSA algorithm. The result of this research is the application generates the reporting before 09.00 H+1 and not have penalty. For data authentication, this application implement RSA algorithm, so data of rekening koran will be valid.